Cost-Benefit Analysis of Discretionary Wars. Issue 1 (1st January 2019) - Hu, Diane; Cooper, Andrew; Desai, Neel; Guo, Sophie; Shi, Steven; Banks, David
Abstract: Policy-makers should perform a cost-benefit analysis before initiating a war. This article describes a methodology for such assessment, and applies it post hoc to five military actions undertaken by the United States between 1950 and 2000 (the Korean War, the Vietnam War, the invasion of Grenada, the invasion of Panama, and the First Gulf War). The analysis identifies three broad categories of value: human capital, economic outcomes, and national influence. Different stakeholders (politicians, generals, industry, etc.) may assign different weights to these three categories, so this analysis tabulates each separately, and then, as may sometimes be necessary, monetizes them for unified comparison.